Multinational tax avoidance associated with leverage, intangibility and profitability on non-US. data - Chen, Rong (2024)
This study investigates the tax avoidance behaviors of multinational corporations (MNCs) by analyzing the effective tax rates (ETRs) of global ultimate owners and their subsidiaries from 2000 to 2022. Using panel data from the Osiris database, this dissertation examines how various subsidiary-level financial metrics, weighted by the inverse of their domestic statutory tax rates, influence the parent firm's book ETR. Key independent variables include the number of subsidiaries in tax havens, intangibility, leverage, profitability, size, and statutory tax differences. The results showed significant negative correlations between the number of tax haven subsidiaries and book ETRs for parent firms. The presence of tax haven subsidiaries amplifies the impact of subsidiary aggregated leverage and size on tax avoidance. The findings underscore the importance of regulatory measures to curb tax avoidance and highlight the need for further research into the tax practices of MNCs in diverse jurisdictions.